2021
DOI: 10.1016/j.ajo.2020.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Teleophthalmology: Evaluation of Phone-based Visual Acuity in a Pediatric Population

Abstract: : Purpose With the recent rise of teleophthalmology due to coronavirus disease, we are in need of accurate and reliable methods of checking visual acuity remotely. We compare the visual acuity as measured by the GoCheck Kids application, HOTV with the amblyopia treatment study (ATS), and our clinic protocol. Design This is a prospective, comparison of visual acuity assessment methods. Methods Established patients (aged 3-18) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
(58 reference statements)
1
21
0
Order By: Relevance
“…COMPlog, a distance VA test requiring a specifically sized computer monitor and trained observer, recorded TRT LOA at ±0.10–0.12 logMAR [ 14 ], and ICC of 0.964 when comparing face to face with remote testing [ 15 ]. Other smartphone-based VA testing apps have reported LOAs of ±0.198 logMAR [ 16 ] and ±0.10-0.30 logMAR under clinical supervision [ 17 ]. Together, these data provide a priori standards by which DigiVis can be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…COMPlog, a distance VA test requiring a specifically sized computer monitor and trained observer, recorded TRT LOA at ±0.10–0.12 logMAR [ 14 ], and ICC of 0.964 when comparing face to face with remote testing [ 15 ]. Other smartphone-based VA testing apps have reported LOAs of ±0.198 logMAR [ 16 ] and ±0.10-0.30 logMAR under clinical supervision [ 17 ]. Together, these data provide a priori standards by which DigiVis can be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Providing the estimation of refraction with valid photorefractors in a drive-by paradigm is a beneficial step. Visual acuity can be checked at home by a phone-based 18 or paper download 19 method. Further referral toward expert pediatric ophthalmic specialty care must be balanced with community needs for pandemic isolation.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important step given that assessment at home introduces more sources of variability. During the COVID-19 pandemic, the use of apps to assess VA at home was evaluated, but one study had a very low participation rate (only 16% of parents that gave consent to participate provided data) (Painter et al 2021), and another reported a modest correlation with clinical tests (Silverstein et al 2021). Therefore, further evaluation of the Amblyopia Tracker app is underway, with parents testing children at home and then testing repeated on return to the clinic.…”
Section: Discussionmentioning
confidence: 99%